1993
DOI: 10.1172/jci116247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oleate-rich and linoleate-rich diets on the susceptibility of low density lipoprotein to oxidative modification in mildly hypercholesterolemic subjects.

Abstract: We report the results of feeding oleate-or linoleate-enriched diets for 8 wk to mildly hypercholesterolemic subjects and the resulting alterations in composition and functional properties of their plasma LDL and HDL. LDL isolated from subjects on oleate-enriched diets was less susceptible to copper-mediated oxidation, as measured by conjugated diene and lipid peroxide formation, and less susceptible to LDL-protein modification, as evidenced by reduced LDL macrophage degradation after copper-or endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
142
2
7

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(164 citation statements)
references
References 32 publications
13
142
2
7
Order By: Relevance
“…Reaven et al [34] showed that the extent of LDL oxidation is strongly influenced by the LDL linoleic acid content. More recently, dietary studies have shown that the enrichment of LDL linoteic acid by dietary manipulation resulted in an increase in oxidisability [35,36]; our results confirm those findings. The diabetic subjects in this study had a raised percentage of linoleic acid in their cholesteryl ester and this positively correlated with oxidisability.…”
Section: Discussionsupporting
confidence: 91%
“…Reaven et al [34] showed that the extent of LDL oxidation is strongly influenced by the LDL linoleic acid content. More recently, dietary studies have shown that the enrichment of LDL linoteic acid by dietary manipulation resulted in an increase in oxidisability [35,36]; our results confirm those findings. The diabetic subjects in this study had a raised percentage of linoleic acid in their cholesteryl ester and this positively correlated with oxidisability.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the change in n-6 PUFAs in serum phospholipids differed significantly between the groups, but the intragroup increase in linoleic acid during 1 y of corn oil treatment did not reach statistical significance. Several studies support the notion that a high intake of n-6 PUFAs may increase lipid peroxidation (Reaven et al, 1991(Reaven et al, , 1993(Reaven et al, , 1994, and may explain the increase over 1 y also in our control group. Therefore, the choice of control in our study may partly mask the effect of n-3 PUFAs intervention.…”
Section: Discussionsupporting
confidence: 84%
“…Polyunsaturated fatty acids are particularly susceptible to peroxidation by free radicals, whereas LDL particles enriched with monounsaturated fatty acids are less prone to oxidative injury [63]. In agreement with these in vitro findings, patients with type 2 diabetes treated with a diet enriched with monounsaturated fatty acids show an increased LDL lag time [64].…”
Section: Measurement Of Ldl Oxidationsupporting
confidence: 54%